A function $f$ is said to have a lower bound $c$ if $c \le f(x)$ for all $x$ in its domain. The definition is similar for sequences.

Now Assume that the sequence $a_n=\sum_{k=1}^{n} \frac{1}{\sqrt k} - 2\sqrt n$ is given.
How can we prove that this sequence has lower bound?

Note : It's much easy to show that the sequence has upper bound. But, my problem is that it seems i have nothing to work on in order to prove the existance of lower bound.

  • $\begingroup$ By the reflection formula for the $\zeta$ function, $$\lim_{n\to +\infty}\left(-2\sqrt{n}+\sum_{k=1}^{n}\frac{1}{\sqrt{k}}\right) = \zeta\left(\frac{1}{2}\right) = -1.4603545088\ldots $$ $\endgroup$ – Jack D'Aurizio Oct 17 '16 at 17:52

Hint: Observe \begin{align} \sum^n_{k=1} \frac{1}{\sqrt{k}} \geq \int^{n+1}_1 \frac{1}{\sqrt{x}}\ dx = 2\sqrt{n+1}-2. \end{align}

  • $\begingroup$ Great !!! How did you think about integration ? $\endgroup$ – Arman Malekzadeh Oct 17 '16 at 17:18

Variation without integration. Going from $n$ to $n+1$ adds $$\begin{eqnarray}\frac1{\sqrt{n+1}}-2\left(\sqrt{n+1}-\sqrt{n}\right) &=& \frac1{\sqrt{n+1}} -\frac2{\sqrt{n}+\sqrt{n+1}}\\ &>& \frac1{\sqrt{n+1}} -\frac1{\sqrt{n}} \end{eqnarray}.$$ Starting at $a_1=-1$ this results in a telescoping sum for $n > 1$ $$\sum_{k=1}^n\frac1{\sqrt{k}} - 2\sqrt{n}>-2+\frac1{\sqrt{n}}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.